Marine Fouling Characteristics of Biocomposites in a Coral Reef Ecosystem (Adv. Sustainable Syst. 9/2021). (17th September 2021) - Contardi, Marco; Montano, Simone; Galli, Paolo; Mazzon, Giulia; Mah'd Moh'd Ayyoub, Amin; Seveso, Davide; Saliu, Francesco; Maggioni, Davide; Athanassiou, Athanassia; Bayer, Ilker S.
Abstract : Coral Reef Restoration In article number 2100089, Marco Contardi, Simone Montanoand, Athanassia Athanassiou and co‐workers fabricate two biodegradable biocomposites based on starch–polydimethylsiloxane and soybean lecithin‐wax‐polyurethane. They are evaluated as scaffolds for the growth of oceanic organisms. Such materials placed underwater on the Maldivian lagoon for six months show biodegradation and the growth of several organisms, including coral larvae.